An introduction to knowledge information strategy : from business intelligence to knowledge sciences - Ishikawa, Akira, 1934-; Nakagawa, Juro, 1935- (World Scientific, 2013)
"This book discusses the essence, concepts, techniques, and applications of business intelligence. It also explores different aspects of crisis management, knowledge management and knowledge sciences, the applications of business intelligence in contingencies and crises, environmental issues and group intelligence. The book is divided into three parts. The first part focuses on the significance of business intelligence, competition and intelligence, competitive information strategy, conflicts on patent issues, and the current state-of-the-art of business intelligence education in the US and France. The second part encompasses business intelligence and risk and crisis management, ecological issues and crisis management, business intelligence and knowledge management, and business intelligence as an organizational knowledge. The third part consists of case studies in business intelligence with special reference to the retail industry and the military arena. This part also focuses on applications of business intelligence. Finally, the book also envisages the future direction of knowledge information strategy. It will be of interest to students, academicians and people working in non-profit or non-government organizations"-- Resumé vydavatele
Přeloženo z japonštiny?
Keywords: business intelligence; znalostní management; competitive intelligence; krizový management; knowledge management; crisis management; příručky; handbooks, manuals, etc